Characterization of the aryl hydrocarbon receptor as a potential candidate to improve cancer T cell therapies - Valentine De Castro; Oumaïma Abdellaoui; Barbara Dehecq; Babacar Ndao; Patricia Mercier-Letondal; Alexandra Dauvé; Francine Garnache-Ottou; Olivier Adotévi; Romain Loyon; Yann Godet (Cancer Immunology, Immunotherapy)
Abstract The efficacy of T-cell-based cancer therapies can be limited by the tumor microenvironment which can lead to T cell dysfunction. Multiple studies, particularly in murine models, have demonstrated the capacity of the aryl hydrocarbon receptor (AHR) to negatively regulate antitumor T cell functions. AHR is a cytoplasmic receptor and transcription factor that was originally identified as a xenobiotic sensor, but has since been shown to play a significant role in the gene regulation of various immune cells, including T cells. Given the insights from murine studies, AHR emerges as a promising candidate to invalidate for optimizing T cell-based cancer therapies. However, the controversial role of AHR in human T cells underscores the need for a more comprehensive characterization of AHR expressing T cells. This study aims to investigate the regulatory mechanisms of AHR in human T cell biology to better understand its impact on reducing antitumor immune responses. Here, we knocked-out AHR in human T cells using CRISPR-Cas9 technology to characterize AHR’s function in an in vitro chronic stimulation model. Engineered T cells exhibited enhanced effector- and memory-like profiles and expressed reduced amount of CD39 and TIGIT. AHR knockout enhanced human CAR-T cells’ functionality and persistence upon tumor chronic stimulation. Collectively, these results highlight the role of AHR in human CAR-T cells efficiency.